Hypertensive disorders of pregnancy. - Jara Mori, Teófilo (2015)
Preeclampsia associated seizures are important cause of maternal morbidity and mortality. Even though the disease is known since antiquity, treatment is still inadequate. Modification of inefficient eclampsia treatment consists in improving training of all gynecologists and obstetricians, anestesiologists, general physicians and midwives in severe preeclampsia and eclampsia diagnosis and treatment. At Maternal Perinatal National Institute we have adopted the American College of Obstetricians and Gynecologists diagnostic criteria expressed in clinical guidelines and procedures for obstetrical care. Treatment objectives consist in controlling arterial hypertension, to prevent seizures occurrence or repetition, to optimize intravascular volume, to maintain adequate arterial oxygenation, early diagnosis and treatment of complications, and ending pregnancy by the fastest route.